Sistem Pendukung Keputusan dalam Menentukan Dosen Pembimbing Skripsi Fakultas Teknik Informatika Universitas Islam Sumatera Utara menggunakan Metode Weighted Product (WP) - Faisal Hasiholan Purba; Antoni Antoni (Journal of Information System Research (JOSH), 2019)
The determination of the thesis supervisor at the Informatics Engineering Study Program at the North Sumatra Islamic University is currently done by determining directly by determining the thesis supervisor to be directed and helping to complete the thesis. The main objective of this research is to Determine the Thesis Supervisor of Engineering, Faculty of Engineering, Islamic University of North Sumatra, the method used in determining the supervisor using the WP (Weighted Product). Making this system begins. Observing and searching for data, Analysis and data collection stage, design, installation Programming and installation of subsequent implementation using the Php programming language and Mysqk database for its database. The final results of this study are the results of a thesis supervisor supervisor's decision support system using the Weight Poduct (WP) method.